2020
DOI: 10.3389/fimmu.2020.01910
|View full text |Cite
|
Sign up to set email alerts
|

Heme Induces IL-6 and Cardiac Hypertrophy Genes Transcripts in Sickle Cell Mice

Abstract: Emerging data indicate that free heme promotes inflammation in many different disease settings, including in sickle cell disease (SCD). Although free heme, proinflammatory cytokines, and cardiac hypertrophy are co-existing features of SCD, no mechanistic links between these features have been demonstrated. We now report significantly higher levels of IL-6 mRNA and protein in hearts of the Townes sickle cell disease (SS) mice (2.9-fold, p ≤ 0.05) than control mice expressing normal human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Conversely, left ventricular hypertrophy (LVH) is found in over 60% of children and 37% in adults with SCD ( 389 , 390 ), with cardiopulmonary complications accounting for about 26% of deaths in adults with SCD ( 391 ). In this current issue and for the first time, our group investigated the expression of plasma and cardiac IL-6 and its inducibility by heme in Townes sickle cell (SS) mouse model ( 392 ). We observed significantly elevated cardiac IL-6 and direct heme induction of circulating and cardiac IL-6 transcripts and protein in SS mice compared to controls.…”
Section: Hemolysis Interleukin-6 and Cardiovascular Dysfunctionmentioning
confidence: 99%
“…Conversely, left ventricular hypertrophy (LVH) is found in over 60% of children and 37% in adults with SCD ( 389 , 390 ), with cardiopulmonary complications accounting for about 26% of deaths in adults with SCD ( 391 ). In this current issue and for the first time, our group investigated the expression of plasma and cardiac IL-6 and its inducibility by heme in Townes sickle cell (SS) mouse model ( 392 ). We observed significantly elevated cardiac IL-6 and direct heme induction of circulating and cardiac IL-6 transcripts and protein in SS mice compared to controls.…”
Section: Hemolysis Interleukin-6 and Cardiovascular Dysfunctionmentioning
confidence: 99%
“…Gbotsho et al recently demonstrated that when the plasma heme scavenging system is saturated, the circulating heme induces a cardiac expression of IL-6 in sickle cell mice through an Nfr2 independent pathway. Even though the underlying mechanisms of heme-induced IL-6 expression still need to be addressed, the authors suggested that this mechanism might involve the TLR-4-MyD88-AP-1 NF-ĸB axis ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gbotosho et al recently suggested that heme induced IL-6 expression and cardiac hypertrophy in patients and mice with sickle cell disease (SCD) ( Gbotosho et al, 2020 ). Heme-laden erythrocyte membrane microparticles triggered rapid vaso-occlusions in kidneys and compromised microvascular dilation ( Camus et al, 2015 ).…”
Section: Cardiac Iron Overloadmentioning
confidence: 99%